Checklisten in der Hausarztpraxis – eine Entwicklungsstudie mit Vorher/Nachher-Vergleich - Saggau, Korbinian; Höfle, Anina; Schedlbauer, Angela; Hueber, Susann; Roos, Marco; Kühlein, Thomas; Heinmüller, Stefan (Zeitschrift für Allgemeinmedizin, 2021)
Background Quality assurance in Germany focuses on support processes (requirements of hygiene etc.) rather than on quality of care (QOC). Systems that do focus on QOC are referred to as “clinical governance” (CG). We understand CG as a process of professional self-reflection and management. An electronic checklist (eCL) for Chronic Obstructive Lung Disease (COPD) was developed reminding doctors of important aspects of care, assuring adequate documentation, and generating data at the same time. We describe the development of the eCL and a before/ after analysis of process-QOC for COPD-patients in a single group family practice. Methods Developmental study with a before/after-analysis. To capture QOC at baseline (t0) electronic health records (EHR) of COPDpatients were surveyed using a guideline-based questionnaire. Our intervention was an eCL, which can be used within the EHR. Doctors and practice assistants were trained in the application of the eCL, its use remained optional. One year (t1) and four years (t2) after implementation QOC was reanalysed. Results At t0 103 COPD patients were identified. For 58% a spirometry was documented. Smoking status was recorded in 56% and 34% were vaccinated against influenza. After introduction of the eCL due to some changes in the practice 80 patients at t1 and 49 patients at t2 were identified. For 71% (t1) and 63% (t2) a spirometry was documented. Smoking status was documented in 75% (t1) and 90% (t2). Influenza vaccination was documented in 33% (t1) and 55% (t2) of patients. Conclusions Development and implementation of an eCL in the setting of our office within the EHR was possible. Our results indicate that the provision of an eCL together with a short introduction can help improve QOC. The eCL allows doctors to perform CG autonomously.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Checklist; Chronic disease; Evidence-based medicine; Family medicine; General practice

Do guidelines help us to deviate from their recommendations when appropriate for the individual patient? A systematic survey of clinical practice guidelines - Morgott, Marc; Heinmüller, Stefan; Hueber, Susann; Schedlbauer, Angela; Kühlein, Thomas (Journal of Evaluation in Clinical Practice, 2019)
Rationale, aims, and objectives: Clinical practice guidelines (CPG) were introduced to summarize the best scientific evidence available. Thereby, CPG were meant to support evidence-based medicine (EBM). However, besides evidence, EBM also asks for patients' preferences and physicians' experiences to be considered when coming to therapeutic decisions. Thus, deviations from CPG recommendations are sometimes necessary when practicing EBM. We wanted to examine whether CPG support deviations from their recommendations when appropriate. For operationalization, we asked whether absolute effect sizes (AES) for benefit and/or harm of suggested therapies were provided along with the respective CPG recommendation. Methods: This systematic survey comprised the most common CPG on chronic coronary heart disease (CCHD) and type 2 diabetes mellitus (T2DM) from English- and German-speaking countries. Only CPG recommendations on pharmacotherapy were evaluated. If AES of a recommended therapy were reported, we rated how easily findable they were within the CPG. Moreover, we assessed whether the CPG provided patient information material and whether this material supplied AES allowing patients to determine the effects to be expected. Results: In the 13 CPG surveyed, 144 recommendations on pharmacotherapy were identified. For 108 recommendations (75%), no AES for benefit and/or harm were reported. Thirty-one recommendations (22%) were accompanied by one or more AES for either benefit or harm. Along with five recommendations (3%), one or more AES for both benefit and harm were given. AES were considered easy to find for three of these 36 recommendations (8%). Patient information material was provided in three of the 13 CPG (23%) accounting for AES in one occasion only. Conclusion: Current CPG on T2DM and CCHD do not sufficiently offer AES for benefits and harms of recommended therapies. Thus, they lack satisfactory information to support deviations from CPG recommendations. Consequently, CPG in their present form do not adequately facilitate EBM.
CRIS-Team Scopus Importer:2019-07-02
Keywords: abolute risk reduction; clinical decision making; evidence-based medicine; patient-centred care; practice guidelines as topic

Laying the foundation for a core set of the International Classification of Functioning, Disability and Health for community-dwelling adults aged 75 years and above in general practice: a study protocol - Tomandl, Johanna; Book, Stephanie; Gotthardt, Susann; Heinmüller, Stefan; Grässel, Elmar; Freiberger, Ellen; Kühlein, Thomas; Hueber, Susann; Hoyer, Stefanie (BMJ Open, 2018)
Introduction With the medical focus on disease, the problem of overdiagnosis inevitably increases with ageing. Considering the functional health of patients might help to discriminate between necessary and unnecessary medicine. The International Classification of Functioning, Disability and Health (ICF) is an internationally recognised tool for describing functional health. However, it is too detailed to be used in primary care practices. Consequently, the aim of this study is to identify relevant codes for an ICF core set for community-dwelling older adults (75 years and above) in primary care. Methods and analysis The study will follow the methodology proposed by the ICF Research Branch to identify relevant concepts from different perspectives: (1) Research perspective: A systematic review of studies focusing on functional health in old age will be conducted in different databases. Relevant concepts will be extracted from the publications. (2) Patients' perspective: Relevant areas of functioning and disability will be identified conducting qualitative interviews and focus groups with community-dwelling older persons. The interviews will be transcribed verbatim and analysed using the documentary method of interpretation. (3) Experts' perspective: An online survey with open-ended questions will be conducted. Answers will be analysed using the qualitative content analysis of Mayring. (4) Clinical perspective: A cross-sectional empirical study will be performed to assess the health status of community-dwelling older adults using the extended ICF checklist and other measurement tools. Relevant concepts identified in each study will be linked to ICF categories resulting in four preliminary core sets. Ethics and dissemination Ethical approval for the study was obtained (90_17B). All participants will provide written informed consent. Data will be pseudonymised for analysis. Results will be disseminated by conference presentations and journal publications. Trial registration number Projektdatenbank Versorgungsforschung Deutschland: VfD_17_003833, Clinicaltrials.gov: NCT03384732 and PROSPERO: CRD42017067784.
EVALuna2:35588

Laying the foundation for a Core Set of the International Classification of Functioning, Disability and Health for community-dwelling older adults in primary care: Relevant categories of their functioning from the research perspective, a scoping review - Tomandl, Johanna; Heinmüller, Stefan; Selb, Melissa; Grässel, Elmar; Freiberger, Ellen; Kühlein, Thomas; Hueber, Susann; Book, Stephanie; Gotthardt, Susann (BMJ Open, 2021)
Objectives The objective of this study was to find relevant concepts of functioning in community-dwelling older adults within frequently used assessment instruments published in the scientific literature. This was part of a larger project to develop an International Classification of Functioning, Disability and Health (ICF) Core Set for use in primary care. Design A scoping review was conducted. Articles dealing with functioning in older adults were searched and assessed for eligibility. The study population included community-dwelling adults (≥75 years) without dementia, living in high-resource countries. Relevant concepts were extracted from assessment instruments and linked to the ICF using standardised linking rules. Finally, a frequency analysis was conducted. Setting Home, primary care. Participants Community-dwelling adults aged 75 years and above. Results From 5060 identified publications, 68 were included and 30 assessment instruments extracted. Overall, 1182 concepts were retrieved. Most were linked to the â € activities and participation' component. The most frequently identified categories were â € memory functions', â € dressing' and â € changing basic body position'. Conclusions This review provides a list of relevant ICF categories from the research perspective that will be used for developing an ICF Core Set for older primary care patients.
CRIS-Team Scopus Importer:2021-03-05
Keywords: general medicine (see internal medicine); geriatric medicine; primary care

The quality of COPD care in German general practice—A cross-sectional study - Heinmüller, Stefan; Schaubroeck, Emmily; Frank, Luca; Höfle, Anina; Höfle, Anina; Langer, Michael; Saggau, Korbinian; Schedlbauer, Angela; Kühlein, Thomas (Chronic Respiratory Disease, 2020)
Objectives: Chronic Obstructive Pulmonary Disease (COPD) is a common health problem to be dealt with in primary care. Little is known about the quality of care provided for patients with COPD in Germany. Therefore, we wanted to assess the current quality of care delivered by a primary care network (PCN) for patients with COPD. Methods: A cross-sectional study was conducted in collaboration with a primary care network (PCN). All patients of the PCN aged 40 years and older with a diagnosis of COPD were identified through electronic health records (EHR). A set of quality indicators (QIs) developed in accordance with current COPD-guidelines were appraised through numerical data retrieved from the EHR. Results: In total, 2,568 patients with COPD were identified. Their mean age was 67 (SD±12) years, 49% were male. Thirty-five percent had a parallel diagnosis of asthma. There was no documentation of any spirometry for 54% of patients; 29% had a spirometry within the previous year. An influenza vaccination was documented for 37% within the preceding 12 months; 12% received a pneumococcal vaccination in the last 6 years. Smoking status was documented for 44% within the last year. Conclusion: The quality of care for patients with COPD in the PCN seemed suboptimal, despite the presence of a Disease Management Program (DMP). This finding is likely to apply widely to German general practice. Quality assessment through currently available EHR data was challenging due to non-standardized and insufficient documentation.
CRIS-Team Scopus Importer:2020-12-11
Keywords: chronic obstructive; documentation; general practice; practice guideline; Pulmonary disease; quality of health care